2019
DOI: 10.1093/gbe/evz111
|View full text |Cite
|
Sign up to set email alerts
|

Avian Binocularity and Adaptation to Nocturnal Environments: Genomic Insights from a Highly Derived Visual Phenotype

Abstract: Typical avian eyes are phenotypically engineered for photopic vision (daylight). In contrast, the highly derived eyes of the barn owl (Tyto alba) are adapted for scotopic vision (dim light). The dramatic modifications distinguishing barn owl eyes from other birds include: 1) shifts in frontal orientation to improve binocularity, 2) rod-dominated retina, and 3) enlarged corneas and lenses. Some of these features parallel mammalian eye patterns, which are hypothesized to have initially evolved in nocturnal envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…cochlearius , are associated with morphologies or functions of ( FOXP2 ) [ 49 ], lens ( SMAD3 ) [ 50 ], cornea ( SLC4A10 ) [ 51 ], retina ( EPAS1 ) [ 52 ], and optic nerve ( OPA1 ) [ 53 , 54 ], respectively. Relaxed selection of these genes may contribute to adjust the morphologies or functions of different eye components to enhance night vision as the finding in a previous study of barn owl ( Tyto alba ) [ 35 ]. In the barn owl, the unique phenotypes of the scotopic-adapted eyes are hypothesized to have evolved through relaxed or intensified selection in genes with predominant roles in different eye elements [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cochlearius , are associated with morphologies or functions of ( FOXP2 ) [ 49 ], lens ( SMAD3 ) [ 50 ], cornea ( SLC4A10 ) [ 51 ], retina ( EPAS1 ) [ 52 ], and optic nerve ( OPA1 ) [ 53 , 54 ], respectively. Relaxed selection of these genes may contribute to adjust the morphologies or functions of different eye components to enhance night vision as the finding in a previous study of barn owl ( Tyto alba ) [ 35 ]. In the barn owl, the unique phenotypes of the scotopic-adapted eyes are hypothesized to have evolved through relaxed or intensified selection in genes with predominant roles in different eye elements [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relaxed selection of these genes may contribute to adjust the morphologies or functions of different eye components to enhance night vision as the finding in a previous study of barn owl ( Tyto alba ) [ 35 ]. In the barn owl, the unique phenotypes of the scotopic-adapted eyes are hypothesized to have evolved through relaxed or intensified selection in genes with predominant roles in different eye elements [ 35 ]. Additionally, the authors suggested that some genes have coevolved with contrasting selective signature due to adaptive compensation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 48 ] and Borges et al . [ 49 ] and used Materialise Mimics angle, distance and plane tools. Orbital margin convergence (OMC) was calculated using the orbit posterior angle (OPA).…”
Section: Methodsmentioning
confidence: 99%
“…2018) . In birds, the genetic basis for nocturnal adaptations has mostly been studied in the visual system of two nocturnal species, the kiwi Apteryx mantelli and the barn owl Tyto alba ( Borges et al 2015 , 2019 ; Le Duc et al 2015 ; Emerling 2018) . Le Duc et al (2015) showed that adaptations to nocturnality in kiwis are associated with an increase in the olfactory receptor repertoire and an accumulation of evolutionary changes in genes related to color vision, mitochondrial function, and energy expenditure.…”
Section: Introductionmentioning
confidence: 99%